Compressive measurement and feature reconstruction method for autonomous star trackers. (December 2016) - Yin, Hang; Yan, Ye; Song, Xin; Yang, Yueneng
Abstract: Compressive sensing (CS) theory provides a framework for signal reconstruction using a sub-Nyquist sampling rate. CS theory enables the reconstruction of a signal that is sparse or compressible from a small set of measurements. The current CS application in optical field mainly focuses on reconstructing the original image using optimization algorithms and conducts data processing in full-dimensional image, which cannot reduce the data processing rate. This study is based on the spatial sparsity of star image and proposes a new compressive measurement and reconstruction method that extracts the star feature from compressive data and directly reconstructs it to the original image for attitude determination. A pixel-based folding model that preserves the star feature and enables feature reconstruction is presented to encode the original pixel location into the superposed space. A feature reconstruction method is then proposed to extract the star centroid by compensating distortions and to decode the centroid without reconstructing the whole image, which reduces the sampling rate and data processing rate at the same time. The statistical results investigate the proportion of star distortion and false matching results, which verifies the correctness of the proposed method. The results also verify the robustness of the proposed method to a great extent and demonstrate that its performance can be improved by sufficient measurement in noise cases. Moreover, the result on real star images significantly ensures the correct star centroid estimation for attitude determination and confirms the feasibility of applying the proposed method in a star tracker. Highlights: The concept of folding is introduced as measuring mechanism. A pixel-based folding model is derived to enable feature reconstruction. An innovative compressive feature reconstruction (CFR) method is proposed. CFR not only reduces the sampling rate but also lowers the rate of data processing.